Nuevas tecnologías y dilemas éticos (2003)
Technology development -specially media technology development- goes extremely faster than Social Development. As a consequence, the role of the human being easily weakens. From a neutral position (not pessimist nor too optimist) the writer analyses some ethic problems recently appeared, and some others to come in the future; recognizing that we are living in a world where daily human activities depend each time more on machines.